"That's what she said": centring women's testimony in rape trials - re-writing Raja and Ors. v. State of State of Karnataka (2016) 10 SCC 506". Issue 3 (2nd September 2021) - Dash, Preeti Pratishruti; Thyagarajan, Rohini; Puri, Tejasvini
ABSTRACT: This paper is an attempt to re-imagine a 2016 Division Bench judgement of the Supreme Court of India in an appeal against conviction for rape, through a feminist dissent. The imaginary dissent is situated in the time and place of when the majority decided the appeal and significantly departs, both methodologically and substantively, from the majority opinion. It does so by according primacy to the complainant's testimony and evaluating it independently of the other evidence on record, including the medical evidence. The accompanying commentary sets the judgement in the context of the socio-legal framework in which it was delivered and highlights the ways in which the dissent demonstrates the possibility of writing a feminist judgment even while adhering to the limits set by applicable law.